Abū Bakr Ibn al-‘Arabī: The Defender of Ash‘arism - Abdul Muthalib (Refleksi: Jurnal Kajian Agama dan Filsafat, 2018)
This paper deals with Abū Bakr Ibn al-‘Arabī’s Ash‘arite theological perspective. He chose to adopt Ash‘arism because he believes that God chose certain figures to safeguard religion and the most important one among them is Abu al-Hasan al-Ash‘arī from whom correct theology spread from one generation of disciples to another. His education at Nidhamiyya College and Abu Hamid al-Ghazali’s tutorship might also be responsible for his preference for Ash‘arism. However, even though he was al-Ghazali’s student, he was not attracted by Sufism, instead keeping his focus on theology. He objected to Sufism for two defects he perceived it to possess. First is Sufis’ references to fake Hadiths and second the Sufi practice of self-mortification. As a devoted Ash‘arite, he consistently opposes the anthropomorphic interpretation of God’s nature espoused by the Hanbalites and the Dhahirite.